The Urgency of Updating Material Legal Sources in the Resolution of Sharia Economic Disputes - Firdaus, Muhammad Irkham; Aziz, Muhammad Abdul; Syakuro, Ardhian Ahmad (Sharia Faculty Islamic Economic Law Study Department, 2025)
Currently, material legal sources within the scope of sharia economic law are still very few. The existing sources of law are still general in sharia banking, even though there are cases of violations in the sharia economy which are also increasing along with the development of the sharia economy in Indonesia. The judge instead uses other sources of substantive law that are not in accordance with the principles of Sharia itself. In fact, the pure sources of substantive law derived from Islamic law do not serve as the primary legal sources, but only as legal opinions and doctrines. The aim of this research is to see the urgency of updating material legal sources in sharia economics. This type of research is qualitative. The results of this research are general facts that updating material legal sources is urgently needed. Because sharia economic violations are increasing, there needs to be a valid and concrete source of sharia economic law that can help resolve these cases. And from the results of other research, the source and legal basis for sharia case decisions still uses the Civil Code.